The Relation Between The Book Of Life With Believers Verse Unbelievers - Elisabeth Sulastri; Sjanette Eveline (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2022)
The first states that the believer's relationship in the book of life is permanently recorded. Jesus emphasized / explained on the status of believers who have been registered in the Book of Life (Luke 10:10, Hebrews 12:23). The Apostle Paul also said that partners in constant and permanent ministry are listed in the Book of Life (Phil. 4:3). The names of erasures from the Book of Life never apply to believers in Christ because believers are secure in Him, kept by the power of God (1 Pet. 1:5) and are safe in the hands of the Father and the Son (John 10:28-30). Second, how do unbelievers relate to our lives? In the book of Psalm 69, is a messianic psalm that describes the suffering of Christ caused by his enemies. Who are the enemies of Christ? Those who reject Him. What David said in Psalm 69:28, about the unbelievers, David said